Chutes and Ladders? Job Opportunities for Generation Covid - Barth, Erling; Dale-Olsen, Harald; Schøne, Pål; Østbakken, Kjersti Misje (Nordic Journal of Working Life Studies, 2024)
Focusing on jobs for youth, this study analyzes the development of job postings in Norway during the first and second waves of the COVID-19 pandemic in 2020. Jobs for youth are defined by the top 20 three-digit occupations for young workers, and postings for these occupations took a heavier hit than other jobs during the pandemic. We also identify the top 20 occupations for entrants immediately after completing their highest education to reveal that, during the pandemic, entry jobs for young people with lower education declined the most. Using 2018 and 2019 as reference years, we show that the decline started before ‘lockdown’ policies were in place but worsened during the lockdown. As the economy reopened, job posting rates improved but did not reach the 2018 and 2019 levels.